Measurement of exclusive γγ→W+W− production and search for exclusive Higgs boson production in pp collisions at √s = 8 TeV using the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (Physical review, 2016)
Searches for exclusively produced W boson pairs in the process pp(γγ)→pW+W−p and an exclusively produced Higgs boson in the process pp(gg)→pHp have been performed using e±μ∓ final states. These measurements use 20.2  fb−1 of pp collisions collected by the ATLAS experiment at a center-of-mass energy √s=8  TeV at the LHC. Exclusive production of W+W− consistent with the Standard Model prediction is found with 3.0σ significance. The exclusive W+W− production cross section is determined to be σ(γγ→W+W−→e±μ∓X)=6.9±2.2(stat)±1.4(sys)  fb, in agreement with the Standard Model prediction. Limits on anomalous quartic gauge couplings are set at 95% confidence level as −1.7×10−6<aW0/Λ2<1.7×10−6  GeV−2 and −6.4×10−6<aWC/Λ2<6.3×10−6  GeV−2. A 95% confidence-level upper limit on the total production cross section for an exclusive Higgs boson is set to 1.2 pb.
Im Titel ist das Plus- und das Minuszeichen hochgestellt
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 15.05.2020
*ATLAS Collaboration: M. Aaboud, C.F. Anders, V. Andrei, C. Antel, A.E. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, E.-E. Kluge, M. Kolb, M. Kretz, A. Kugel, V.S. Lang, M. Lisovyi, K. Meier, H. Meyer zu Theenhausen, D.I. Narrias Villar, M. Sahinsoy, S. Schaetzel, V. Scharf, A. Schoening, H.-C. Schultz-Coulon, D. Sosa, R. Stamen, P. Starovoitov, S. Suchek, M. Wessels [und 2860 weitere Personen]